Isogeometric Methods for Numerical Simulation - Beer, Gernot; Bordas, Stéphane (CISM International Centre for Mechanical Sciences, Courses and Lectures, 2015)
The book presents the state of the art in isogeometric modeling and shows how the method has advantaged. First an introduction to geometric modeling with NURBS and T-splines is given followed by the implementation into computer software. The implementation in both the FEM and BEM is discussed.